The Interference Made by Students to Pronounce English Phoneme in Wajo Buginese Context of South Sulawesi - Hasnawati Hasnawati; Nurdevi Bte Abdul; Darlina Darlina (Institut Agama Islam Negeri Palopo, 2021)
This study was aimed at finding out the factors of Buginese students’ interference in pronouncing English phonemes at the Eleventh Grade of SMA Negeri 1 Majauleng. The research applied a descriptive research method. The subjects of this research were Wajo Buginese students at eleventh grade of senior high school at Wajo regency in South Sulawesi. They were chosen by using purposive sampling technique, and there were 20 students involved in this study. The instrument of the research was pronunciation test and reading test form and. The students’ pronunciation in reading test was recorded to be analyzed based on research focused. The results of this research showed that most of the students were difficult to pronounce the front vowels correctly, it indicated that the interference of made by Wajo Buginese students in pronouncing English phoneme occur in substitution of phoneme and the phoneme that has prominent interference was /ae/. Therefore, students’ dialect of Wajo Buginese interfered English pronunciation in reading.